2017
DOI: 10.1111/1744-9987.12576
|View full text |Cite
|
Sign up to set email alerts
|

Residual Renal Function in Hemodialysis and Inflammation

Abstract: Residual renal function (RRF) has an important effect on uremic toxin clearance, on volume control, on quality of life, and on mortality. In patients with chronic kidney disease (CKD), microinflammation with an increased percentage of CD14 /CD16 inflammatory monocytes has been reported, even with no clinical evidence of inflammation. No correlation has been established between these and RRF in hemodialysis (HD) patients. Our objective was to assess the relationship between RRF and the inflammatory parameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
3
17
1
Order By: Relevance
“…Patients with KRU < 0.5 mL/min had significantly higher β2M levels than those with KRU of 0.5–1 mL/min (28.2 ±6.2 vs 23.1 ±4.6 mg/L, P < 0.001), suggesting that even low levels of RKF may be beneficial. Similar results were reported in another study where patients with RKF were found to have significantly lower levels of β2M …”
Section: Effect Of Rkf On Solute Clearancesupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with KRU < 0.5 mL/min had significantly higher β2M levels than those with KRU of 0.5–1 mL/min (28.2 ±6.2 vs 23.1 ±4.6 mg/L, P < 0.001), suggesting that even low levels of RKF may be beneficial. Similar results were reported in another study where patients with RKF were found to have significantly lower levels of β2M …”
Section: Effect Of Rkf On Solute Clearancesupporting
confidence: 90%
“…A cross‐sectional observational study by de Sequera et al . found that higher RKF was associated with lower levels of inflammatory parameters . A lower percentage of CD14+/CD16++ inflammatory monocytes (14.6% vs 28.3%, P = 0.02) and lower concentrations of C‐reactive protein (CRP) (6.2 vs 21.4 mg/L, P = 0.038) were found in patients with KRU >1 mL/min and diuresis >100 mL/day.…”
Section: Rkf and Inflammationmentioning
confidence: 96%
“…The results of our study, as well as those of Yang and several other authors, confirm that in maintenance HD patients, the concentration of the inflammatory markers such as hs-CRP, IL-6, and TNF-α were significantly lower than that of patients with residual renal function. 16,17 Our results are also consistent with Yang's and Vanitha's results, and high serum TNF-α concentration in HD patients was common, but our TNF-α level was higher than the results of the other studies. However, this result requires further explanation.…”
Section: Discussionsupporting
confidence: 91%
“…54 Moreover, persisting hypervolemia leads to high ultrafiltration rates with increased risk for hemodynamic instability during dialysis 50 resulting in intra-dialytic tissue hypoxia in the gut, in the myocardium, in the brain and elsewhere. 50,53,[55][56][57][58] The propensity to low-degree inflammation seems to be also associated with residual renal function 59 probably partly due to the potential contribution of the latter to volume control. Additional mechanisms for the development of chronic inflammation on hemodialysis may include oxidative and carbonyl stress, impaired pro-inflammatory cytokine clearance, comorbidities, and dialysis-related factors such as bio-incompatibility, water quality, and vascular access type.…”
Section: Parameters and Bis: Can Objective Measures Replace Sga In Amentioning
confidence: 99%